The Role of Law in Tackling Child Exploitation in Child Social Welfare Institutions (LKSA): A Case Study of the Fulfilment of Children's Basic Needs According to Welfare Standards - Ricky Banke; Rolib Sitorus; Joy Zaman Felix Saragih; Andy Tonggo Michael Sihombing (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Child exploitation within Child Social Welfare Institutions (Lembaga Kesejahteraan Sosial Anak or LKSA) remains a significant concern that undermines the fulfillment of children's fundamental rights, particularly in relation to access to education, health care, proper care, and protection. This study aims to examine the role of legal frameworks in preventing and addressing exploitative practices within LKSAs, focusing on the extent to which these institutions ensure the fulfillment of children's basic needs in accordance with national welfare standards. Employing a qualitative research design with a case study approach, the study was conducted in several LKSAs in Medan, North Sumatra. Data collection methods included in-depth interviews with key stakeholders, analysis of relevant legal and institutional documents, and direct field observations. The results show that there are still practices of child exploitation in several LKSA, including forced labor and misuse of foster child status for economic interests. Other important findings include weak supervision by government agencies, limited coordination between agencies, and a lack of understanding by LKSA managers of children's rights. On the other hand, the role of the police as law enforcers is considered reactive and not optimal in preventing and prosecuting cases of child exploitation in LKSA. The main obstacles faced by POLRI include limited resources, lack of specialized training, and the absence of strong synergy between the police and other child protection agencies. Hence, the research emphasizes that although the legal framework is in place through various laws and regulations, its implementation is still not effective.